EVALUASI PENGENDALIAN INTERN PADA PROSES PEMBERIAN KREDIT MODAL KERJA PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK UNIT CAKKE CABANG ENREKANG. - Fajrah Yana; Muchran Bl; Ismail Badollahi (INVOICE : JURNAL ILMU AKUNTANSI, 2019)
This research has the goal to understand the implementation of the system and procedure granting working capital credit and internal control on PT BRI unit cake branch enrekang. The type of research is descriptive qualitative. The data is primary and secondary data. The collection of data using interviews and observation. The result oh this research describe several weaknesses in the system and procedures and internal control in PT BRI unit cake branch enrekang. Based on the results from the study, then suggested that there is no double on account of officer, adding from sheets ceklist, and should be done in internal control supervision document or file-file routinely.